Qard Al Hasan: Instrumen Moneter Syariah Dalam Peningkatan Kesejahteraan Masyarakat Indonesia - Rini, Nova (LPPM Universitas Islam 45, 2023)
Conventional interest-based monetary policy has yet to be effective in overcoming monetary problems. So, this article is to discuss how to apply qard al hasan as one of the sharia monetary instruments in Indonesia. The method used is literature study. The results of the analysis and discussion show that Qard al Hasan's Monetary Policy can be implemented in Indonesia. This is because Qard al Hasan is very in accordance with the Qur'an and Hadith and the implementation of Qard al Hasan-based monetary policy can not only stabilize prices and inflation, but also can increase national production or GDP and reduce the number of poor people. Bank Indonesia as the executor of Monetary Policy can apply the Qard al Hasan system, because Bank Indonesia has started to create a database of community groups that have Micro, Small and Medium Enterprises, so that the implementation of Qard al Hasan in Indonesia can be implemented.